Are Immigrant Remittance Flows a Source of Capital for Development? - Jahjah, Samir (IMF Working Papers; Working Paper ;, 2003)
The role of remittances in development and economic growth is not well understood. This is partly because the literatures on the causes and effects of remittances remain separate. We develop a framework that links the motivation for remittances with their effect on economic activity. Because remittances take place under asymmetric information and economic uncertainty, there exists a significant moral hazard problem. The implication is that remittances have a negative effect on economic growth. We test this prediction using panel methods on a large sample of countries. The results indicate that remittances do have a negative effect on economic growth, which indicates that the moral hazard problem in remittances is severe.